Nitrogen and phosphorus levels affected plant growth, essential oil composition and antioxidant status of lavender plant (Lavandula angustifolia Mill.) - Chrysargyris, Antonios; Panayiotou, Christakis; Tzortzakis, Nikos G. (My University, 2016)
Lavandula angustifolia (Mill.) is a multidisciplinary medicinal and aromatic plant of great importance in fragrance and pharmaceutical industries and/or landscaping. Minerals rate affect yield and quality of medicinal plants therefore, this experiment was conducted in order to determine the effects of nitrogen (N: 150-175-200-225-250 mg/L) and phosphorus (P: 30-40-50-60-70 mg/L) levels on the morphological and biochemical characteristics of lavender under hydroponic condition. The results indicated that P levels mainly affected plant growth, while lower N levels (150 mg/L) reduced chlorophylls content. Essential oil yield was remained unaffected under N and P levels. The N levels greater than 200 mg/L as well as 60 mg/L of P, benefited antioxidant status (total phenols, DPPH, FRAP, flavonoids). The main constituents of leaves essential oil (1.8-cineole, borneol, camphor, α-terpineol, myrtenal) and mineral accumulation were affected by N and P treatments.
Keywords: Antioxidants; Essential oil; Lavandula angustifolia; Mineral accumulation; Soilless culture